FA'ALIYAH ISTIKHDAM TATBIQ 'EDUCANDY' FI TARQIYAT HIFZ AL-MUFRADAT LI THULLAB SOFFI AT-TASI’ BI-MADRASATI PRIK MUNICIPALITY SCHOOL AL-MUTAWASITHOTI AL-HUKUMIYYAH TAYLANDIYYAH - Dewi Qotrun Nada Najwa; Natsaree Rosack; Erma Suryani; Muhammad Syarifuddin (El-Tsaqafah : Jurnal Jurusan PBA, 2025)
The purpose of this study is to determine the effectiveness of using Educandy Application in improving students' vocabulary memorization at Prik Municipality School Thailand. This research is a quantitative research, with a pre experimental research design in the form of one group pre-test and post-test. The population in this study were all students of class IX, while the sample in this study were students of class IX A. Data analysis techniques used in processing data are normality test and t-test. Statistical analysis in this study using SPSS. The results of this study are from the results of the t-test, both seen from the sig value. (2-tailed) which is 0.000 <0.05. Nor the results of T count> T table, namely (9.925> 2.101). Thus it is stated that Ho is rejected and Ha is accepted in this study. So it can be concluded that The educandy app is effective in improving vocabulary memorization for ninth grade students at Prik Municipality School in Thailand. The research demonstrate that the use of the Educandy application significantly improves students' vocabulary retention. This highlights the importance of integrating interactive, game-based technologies into Arabic language learning. In real-world settings, these results suggest that employing such tools can create more engaging and motivating learning environments, particularly in multilingual and multicultural contexts like Thailand. Moreover, this research opens possibilities for further studies focusing on the impact of similar educational applications on other language skills, such as speaking and writing, and across different age groups and educational levels.